Advances in the green synthesis and agrichemical applications of oxathiapiprolin derivatives - Li, Tingting; Jin, Jiamiao; Song, Jia; Lv, Jie; Jin, Zhichao (Frontiers in Chemistry, 2022)
Oxathiapiprolin was developed with high antifungal activity and novel target protein and used in the oomycetes control for the crop protection. The structural modifications of oxathiapiprolin are summarized. The achievements and challenges in the structural modification of oxathiapiprolin are also discussed in this mini review. The outlook in this field is perspected according to our own opinion and understanding on the development of OSBPI (Oxysterol Binding Protein Inhibition) fungicides.